2004
DOI: 10.1002/j.1939-4640.2004.tb02782.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Ram Semen Facilitates Sperm DNA Damage: Relationship Between Sperm Andrological Parameters and the Sperm Chromatin Structure Assay

Abstract: ABSTRACT:We hypothesized that cryopreservation and incubation in conditions that mimic the female genital tract following insemination increases the susceptibility of ram sperm DNA to denaturation. Ram sperm samples (n ϭ 12) underwent the sperm chromatin structure assay (SCSA) and semen quality tests, including motility parameters, viability, and chlortetracycline fluorescence (CTC) patterns. We also assessed correlations between SCSA variables and semen quality parameters. Analyses were performed for both fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 50 publications
(69 reference statements)
5
63
0
5
Order By: Relevance
“…2 Comet image of sperm with fragmented and non fragmented DNA damage as quantified by TUNEL assay. The DNA fragmentation Index, evaluated by SCSA assay, provides a weak or a moderate correlation with conventional sperm parameters (Giwercman A et al, 2003 andPeris SI et al 2004 [103,104]). …”
Section: Clinical Aspects and Relevance Of Dna Integrity Testsmentioning
confidence: 99%
“…2 Comet image of sperm with fragmented and non fragmented DNA damage as quantified by TUNEL assay. The DNA fragmentation Index, evaluated by SCSA assay, provides a weak or a moderate correlation with conventional sperm parameters (Giwercman A et al, 2003 andPeris SI et al 2004 [103,104]). …”
Section: Clinical Aspects and Relevance Of Dna Integrity Testsmentioning
confidence: 99%
“…Frozen semen is easily available for routine use, and some authors argued that early embryo development is not influenced by the method of semen preservation [132], whereas others demonstrated that fresh semen could improve embryo production rates and quality [50]. Eventually, freezing and thawing disrupt the stability of ram sperm chromatin, reducing its fertilization efficiency [133,134]. On the contrary, cryopreserved semen is also advantageous, as it can be stored in seasonal propitious period.…”
Section: In Vitro Fertilization (Ivf)mentioning
confidence: 99%
“…The SCSA predicts infertility when the DFI exceeds 30% in natural conception (Evenson et al 2002, Evenson andWixon 2008), justifying its clinical application. The SCSA has identified compromised chromatin integrity of cryopreserved spermatozoa from different farm animals, such as the boar (Evenson et al 1994), bull (Janaskauska et al 2001) and ram (Peris et al 2004).…”
Section: Chromatin and Dna Integritymentioning
confidence: 99%